2021
DOI: 10.1002/phar.2535
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dosing strategies and trough concentrations of vancomycin in patients undergoing continuous venovenous hemofiltration

Abstract: Study Objective: Recommendations regarding vancomycin dosing in critically ill patients on continuous venovenous hemofiltration (CVVH) are limited. The purpose of this study was to evaluate current dosing practices of pharmacists for patients treated with CVVH, develop guidelines for optimal dosing and monitoring of vancomycin to improve target trough attainment, and reduce pharmacist workload.Design: A retrospective cohort study. was performed of critically ill adult patients from January 2015 to December 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Previous studies have evaluated various vancomycin dosing strategies in CRRT but without consistent results regarding dosing or factors that may impact resultant vancomycin concentrations. [10][11][12] Furthermore, available literature is limited by small numbers of patients, evaluation of only a single vancomycin dose, inconsistent CRRT modalities, or evaluation in pediatric populations.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have evaluated various vancomycin dosing strategies in CRRT but without consistent results regarding dosing or factors that may impact resultant vancomycin concentrations. [10][11][12] Furthermore, available literature is limited by small numbers of patients, evaluation of only a single vancomycin dose, inconsistent CRRT modalities, or evaluation in pediatric populations.…”
Section: Introductionmentioning
confidence: 99%
“…CRRT consists of continuous venovenous hemofiltration (CVVH), continuous venovenous hemodialysis (CVVHD), and continuous venovenous hemodiafiltration (CVVHDF). CVVH is a widely used mode in clinical practice [6], which can effectively remove most of the metabolites, as well as inflammatory mediators, toxins and other macromolecular substances. Meanwhile, CVVH can also remove some drugs by convection and ultrafiltration at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Scheduled vancomycin dosing regimens of 15–22 mg/kg every 12–24 h were required to yield trough levels in the 15–20 mcg/mL range. They concluded that target vancomycin trough achievement of 15–20 mcg/mL occurred more frequently when vancomycin was scheduled at a dose of 15–22 mg/kg every 12–24 h based on the ultrafiltration rate and may alleviate the time and cost associated with frequent vancomycin serum monitoring [ 74 ].…”
Section: Antibiotics In Crrtmentioning
confidence: 99%